Code Mixing Used In Sby's Political Speeches Period 2009 - 2014 - Nuryanto, Sri; , Drs. Marpuji Ali, M.SI; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
Code mixing is condition when speaker mixes one language with another in their speaking activities. This research focuses on the code mixing used in SBY's political speeches period 2009 - 2014. This research is aimed to describe language form used in SBY's political speeches. It is also aimed to examine the factors that cause code mixing in SBY's speeches. The type of research is descriptive qualitative research. Object of research is language form of code mixing used in SBY's political speeches of the period 2009 - 2014 and the factors that cause those codes mixing. Data are the sentences that contain code mixing in SBY's political speeches that is published in presidenri.go.id in September 2013. In collecting data, the writer uses documentation technique. The writer collects the data from the site presidenri.go.id. The findings show that the language form consists of word: noun (23,26%), verb (5,81%), adjective (2,32%); compound noun (18,60%); phrase: noun phrase (33,72%), verb phrase (3,49%) , and infinitive phrase (3,49%); compound noun - phrase (1,16%); Clause (2,32%); hybridization (4,65%); And gradual comparison of adjective (1,16%). Noun phrase dominates language form of code mixing in SBY's speeches. Factor causing code mixing in SBY's speech consists of internal factors: low frequency of word (5,81%), and pernicious homonymy (1,16%); and external factors: introduction and development new culture (13,95%), insufficiently differentiated (5,81%), social value (59,30%) and oversight (13,95%). Social value dominates factor causing code mixing in SBY's speeches.